CP-008 Comparison of prescription profile of antiretroviral drugs between 2014 and 2016 in a tertiary care hospital. (25th February 2017) - Molina, E; Nieto, P; Franco, B; Cañizares, S; Tauste, B; Sierra, F
Abstract : Background: Antiretroviral therapy for the treatment of human immunodeficiency virus type 1 infection has improved steadily since the advent of combination therapy. Purpose: To compare the prescription patterns of antiretroviral therapy between 2014 and 2016. Material and methods: Antiretroviral therapies used in 2014 were compared with those used in 2016 in patients affiliated with a tertiary care hospital in the Spanish Health System. Data were collected from the medication consumption files of the institution. Results: 604 patients were treated in 2014 using 71 different combinations compared with 618 patients treated with 76 combinations in 2016. The percentage of men was 73% in both years. Total expenditure was €4 358 576 in 2014 and €4 414 864 in 2016, with an average cost per patient of €7216 and €7144, respectively. The 10 most common combinations of 2014 were used to treat 73.51% of patients, accounting for 69.31% of the total spending on antiretrovirals whereas the top 10 combinations of 2016 accounted for 78.64% of patients and 74.51% of the total spending. Some of these combinations were in the top 10 in 2014 but not in 2016. Similarly, some new combinations reached the top 10 in 2016. Taken together, 14 combinations were analysed in order. The change in number and per cent of patients with these combinations between 2014 and 2016 were as follows: emtricitabine/tenofovir/efavirenz (155 (25.66%), 91 (14.72%)), emtricitabine/tenofovir/rilpivirine (64 (10.60%), 117 (18.93%)), emtricitabine/tenofovir/lopinavir/ritonavir (52 (8.61%), 6 (0.97%)), emtricitabine/tenofovir/atazanavir/ritonavir (48 (7.95%), 16 (2.59%)), emtricitabine/tenofovir/darunavir/ritonavir (28 (4.64%), 15 (2.43%)), emtricitabine/tenofovir/nevirapine (25 (4.41%), 17 (2.75%)), emtricitabine/tenofovir/raltegravir (22 (3.64%), 27 (4.37%)), darunavir/ritonavir (18 (2.98%), 10 (1.62%)), lopinavir/ritonavir (16 (2.65%), 6 (1.29%)), abacavir/lamivudine/nevirapine (16 (2.65%), 8 (1.29%)), emtricitabine/tenofovir/elvitegravir/cobicistat (0 (0.00%), 95 (15.37%)), abacavir/lamivudine/dolutegravir (0 (0.00%), 84 (13.59%)), dolugravir/rilpivirine (0 (0.00%), 14 (2.27%)) and emtricitabine/tenofovir/dolutegravir (0 (0.00%), 10 (1.62%)). Conclusion: Changes made from 2014 to 2016 have permitted a slight decrease in cost per patient. Emtricitabine/tenofovir based therapies continue to be the backbone of antiretroviral therapy. A large decrease in the use of protease inhibitors in favour of integrase inhibitor family agents was observed, probably due to their better interaction pattern and metabolic profile. References and/or acknowledgements: We thank Torrecardena´s hospital pharmacists for their support. No conflict of interest